Image segmentation of X-Ray and optical images using U-Net/UNet++ based deep learning architecture - Sharma, Tanmoyee; Tabassum, Zaharat; Banik, Ritu; Rahman, S.M.Arifur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021